Lettuce and water spinach growth in silver catfish (Pangasius Sp) culture using aquaponic system - Yuli Andriani; Zahidah Zahidah; Yayat Dhahiyat; Herman Hamdani; Ristiana Dewi (Jurusan Agroteknologi, 2020)
Solid and liquid wastes from feces and fish feed residues can affect water quality, which in turn affect fish physiological processes, behavior, growth and mortality. So it is necessary to have water quality management in the aquaponic system. This study aimed to observe the growth of lettuce and water spinach as biofilters in silver catfish culture (Pangasius sp) using aquaponic system. The study was conducted at the Laboratory of Fisheries, Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran, from March to April 2018. This was an experimental study using Randomized Block Design (RBD) with two treatments and six repetitions to compare between combination of silver catfish and water spinach with silver catfish and lettuce combination. The parameters observed were fish growth, fish survival, increase in stem length, and increase in the number of leaves. The results show silver catfish and water spinach combination produced the highest crop with a stem length of 38.7 cm and more leaves with an addition of 16 leaves. A higher absolute growth of 7.79 grams fish-1 and 100% survival are also seen in this combination. Furthermore, water spinach is more effective as biofilter for aquaponic systems than lettuce.Limbah padat dan cair dari feses dan sisa pakan ikan dapat mempengaruhi kualitas air, yang selanjutnya memengaruhi proses fisiologis ikan, perilaku, pertumbuhan, dan angka kematian. Sehingga perlu adanya manajemen kualitas air pada sistem akuaponik. Penelitian ini bertujuan untuk mengamati pertumbuhan selada dan kangkung sebagai biofilter pada budidaya ikan lele (Pangasiussp) dengan sistem aquaponik. Penelitian dilaksanakan di Laboratorium Perikanan, Fakultas Perikanan dan Ilmu Kelautan Universitas Padjadjaran dari bulan Maret hingga April 2018. Penelitian ini merupakan penelitian eksperimental dengan menggunakan Rancangan Acak Kelompok (RAK) dengan dua perlakuan dan enam ulangan untuk membandingkan kombinasi Ikan Patin dan kangkung dengan kombinasi lele dan selada. Parameter yang diamati adalah pertumbuhan ikan, kelangsungan hidup ikan, pertambahan panjang batang, dan pertambahan jumlah daun. Hasil penelitian menunjukkan Kombinasi lele perak dan kangkung menghasilkan tanaman tertinggi dengan panjang batang 38,7 dan daun lebih banyak dengan penambahan 16 helai daun. Pertumbuhan absolut yang lebih tinggi sebesar 7,79 g ikan-1 dan kelangsungan hidup 100% juga terlihat pada kombinasi ini. Dengan demikan kangkung merupakan biofilter yang lebih efektif untuk aquaponik dibandingkan selada.